Cardiac Calcifications in Adults with Congenital Heart Defects. (7th January 2015) - Halpern, Dan G.; Steigner, Michael L.; Prabhu, Sanjay P.; Valente, Anne Marie; Sanders, Stephen P.
Abstract Objective We investigated the type and extent of calcification in a series of heart specimens from adult congenital heart disease patients because recent autopsy observations suggested a high prevalence of calcification. Design We used computed tomography to examine seven heart specimens from adults (>18 years old) with a congenital heart defect collected with permission from the family during a recent 3‐year period. Clinical data regarding diagnosis, history, and imaging studies were recorded. The 3D data sets were reviewed after reformatting as maximum intensity projection and volumetric renderings to determine the pattern and extent of calcium deposition. Results Five of the seven hearts had extensive calcifications in one or more of three patterns: atherosclerosis associated in the three oldest cases; surgery associated in four of five hearts that had undergone heart surgery; and myocardial calcification remote from surgical sites in two cases. Myocardial calcification was associated with regional dysfunction and was present in the three patients that died suddenly and unexpectedly. Conclusion Cardiac calcification was frequent in our series of heart specimens from adults with congenital heart defects, was often but not uniformly associated with prior surgery, and, in our small series, was associated with regional dysfunction and sudden death.